2014
DOI: 10.3762/bjoc.10.96
|View full text |Cite
|
Sign up to set email alerts
|

Visible light mediated intermolecular [3 + 2] annulation of cyclopropylanilines with alkynes

Abstract: SummaryIntermolecular [3 + 2] annulation of cyclopropylanilines with alkynes is realized using visible light photoredox catalysis, yielding a variety of cyclic allylic amines in fair to good yields. This method exhibits significant group tolerance particularly with heterocycles. It can also be used to prepare complex heterocycles such as fused indolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 42 publications
0
31
0
1
Order By: Relevance
“…We selected this pair of substrates because both were extensively studied in the initial development of the annulation reaction. 9,10 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected this pair of substrates because both were extensively studied in the initial development of the annulation reaction. 9,10 …”
Section: Resultsmentioning
confidence: 99%
“…The scope of this reaction was later expanded to include various pi bonds. 10 These results have opened new avenues for the use of aniline-substituted cyclopropanes as synthetic building blocks. 11 Mechanistically, these methods are all believed to proceed through ring opening of the amine radical cations of N- cyclopropylanilines.…”
Section: Introductionmentioning
confidence: 99%
“…Homolytic decomposition modes are far less common, [43][44][45] although only small amounts of ring strain are necessary to drive C-C bond scission as seen in our efforts converting catharanthine (4.2 kcal/mol ring strain) into Aspidosperma and Iboga alkaloids. 46 Zheng and co-workers have demonstrated the viability of cyclopropane fragmentations within photoredox catalysis, coupling oxidized anilinocyclopropanes with a variety of styrenes, 47 arylacetylenes, 48 diynes, and enynes. 49 The goal of this work was to harness the unique capabilities of photoredox catalysis to generate 1-aminoNBs as a means of addressing the need for new, saturated building blocks in drug discovery.…”
Section: As Illustratedmentioning
confidence: 99%
“…For instance, we have reported that 2 is uniquely capable of promoting radical cation mediated Diels–Alder cycloadditions [ 12 ], radical thiol–ene couplings [ 13 14 ], and photooxygenation reactions [ 15 16 ]. Similarly, Zheng has reported oxidatively initiated indole synthesis [ 17 ] and [3 + 2] cycloaddition [ 18 19 ] reactions using photocatalyst 2 . Finally, a variety of transition metal complexes bearing bipyrazyl ligands have been prepared and investigated for a wide range of applications in inorganic and organometallic chemistry [ 20 25 ].…”
Section: Resultsmentioning
confidence: 99%